THE STUDY OF PREFERENCES OF INABITANTS OF THE CITY OF KEMEROVO AS FAR AS CONSUMER PROPERTIES OF PRODUCTS OF PUBLIC CATERING IS CONCERNED - Ozherel'eva A.V.; Kurakin M.S. (Техника и технология пищевых производств)
The scope of the enterprises of the food service industry in Russia today is represented by a wide range of organizations with different levels of quality and product range, as well as the variety of services offered. Catering is one of the promising business of the consumer market. Under conditions of strong competition it is necessary to realize your customers’ needs, and what properties of products sold by the enterprises of public catering are of paramount importance to ensure the successful operation of the enterprises of the food service industry. The aim of our research is identification of key consumer properties of products produced by public catering enterprises of different types (by the example of the inhabitants of the city of Kemerovo). The objects of study are consumer characteristics of products of commercial catering (restaurants, cafes, fast-food restaurants, etc.) and those of social sectors (cafeterias in educational institutions and hospitals etc.). The study of consumer preferences was conducted using questionnaires. The survey of inhabitants of Kemerovo was carried out in the streets of the city by personal interview lasting 10-15 min. Using the method of the survey 23 basic consumer properties of products have been identified. It has been established that during the year 60% of the inhabitants regularly visit enterprises of the food service industry. According to the results of the survey it has been revealed that the products ordered by a customer (a guest) at the enterprise of the food service industry in the commercial sector should have, in the first place, the following features: beautiful design, flavour and overall quality. Products selected at the foodservice enterprise of the social sphere should be tasty and fresh and have reasonable prices.